2019
DOI: 10.1080/19768354.2019.1626280
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of three different protocols for cholinergic neuron differentiation in vitro using mesenchymal stem cells from human dental pulp

Abstract: A decrease in the activity of choline acetyltransferase, the enzyme responsible for acetylcholine synthesis in the cholinergic neurons cause neurological disorders involving a decline in cognitive abilities, such as Alzheimer’s disease. Mesenchymal stem cells (MSCs) can be used as an efficient therapeutic agents due to their neuronal differentiation potential. Different source derived MSCs may have different differentiation potential under different inductions. Various in vitro protocols have been developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Evaluation of these minimal features has been the basis for selecting cells for in vitro and in vivo experimental purposes. DPSCs displayed high stemness features in accordance with the previously published reports [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Evaluation of these minimal features has been the basis for selecting cells for in vitro and in vivo experimental purposes. DPSCs displayed high stemness features in accordance with the previously published reports [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…After getting donor's consent and approval from the committee for clinical research at GNUCH (GNUCH-2018-11-002), samples were aseptically transported to the laboratory within 3-4 hours. Dental pulp-derived cells were isolated according to the previously published protocol [ 16 ]. Briefly, dental pulp tissues ( n = 5) were carefully separated from the extracted wisdom tooth using a sterile scalpel, gently washed several times with 1% penicillin-streptomycin (10,000 IU and 10,000 μ g/ml, respectively; Pen-Step, Gibco Life Technologies) containing sterile Dulbecco's phosphate-buffered saline (DPBS), and then minced into small pieces using fine surgical blades.…”
Section: Methodsmentioning
confidence: 99%
“…Effectively, MenSCs-derived ChLNs signi cantly expresses cholinergic markers ChAT -the enzyme that catalyzes the biosynthesis of ACh [29], and VAChT -the ACh neurotransmitter transporter [16], two unique markers for cholinergic neurons according to WB, IMF, and FC analysis. In agreement with others, who have demonstrated that MSCs from dental pulp [30], adipose tissue [31], and UC-WJ [12] can transdifferentiate into ChNs/ ChLNs, we show that MenSCs readily transdifferentiated into functional ChLNs. Similar to UC-WJ-MSCs-derived ChLNs [12], the MenSCs-derived ChLNs are responsive to ACh stimuli on days 4 and 7.…”
Section: Discussionsupporting
confidence: 93%
“…Effectively, MenSCs-derived ChLNs signi cantly expresses cholinergic markers ChAT -the enzyme that catalyzes the biosynthesis of ACh [29], and VAChT -the ACh neurotransmitter transporter [16], two unique markers for cholinergic neurons according to WB, IMF, and FC analysis. In agreement with others, who have demonstrated that MSCs from dental pulp [30], adipose tissue [31], and UC-WJ [12] can transdifferentiate into ChNs/ ChLNs, we show that MenSCs readily transdifferentiated into functional ChLNs. Similar to UC-WJ-MSCs-derived ChLNs [12], the MenSCs-derived ChLNs are responsive to ACh stimuli on days 4 and 7.…”
Section: Discussionsupporting
confidence: 93%